2022
DOI: 10.1038/s41598-022-23057-4
|View full text |Cite|
|
Sign up to set email alerts
|

Fabrication of biodegradable chicken feathers into ecofriendly-functionalized biomaterials: characterization and bio-assessment study

Abstract: This study aims to investigate novel applications for chicken feather waste hydrolysate through a green, sustainable process. Accordingly, an enzymatically degraded chicken feather (EDCFs) product was used as a dual carbon and nitrogen source in the production medium of bacterial cellulose (BC). The yield maximization was attained through applying experimental designs where the optimal level of each significant variable was recorded and the yield rose 2 times. The produced BC was successfully characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
2
0
1
Order By: Relevance
“…La adsorción de metales pesados ha emergido como una estrategia rentable, sencilla y confiable en diversas aplicaciones comerciales. La eliminación de estos metales no solo constituye una solución eficaz para reducir costos, sino que también promueve prácticas sostenibles y eco amigables generando beneficios, tanto en el ámbito económico como en el ambiental (Goda et al, 2022).…”
Section: Discussionunclassified
“…La adsorción de metales pesados ha emergido como una estrategia rentable, sencilla y confiable en diversas aplicaciones comerciales. La eliminación de estos metales no solo constituye una solución eficaz para reducir costos, sino que también promueve prácticas sostenibles y eco amigables generando beneficios, tanto en el ámbito económico como en el ambiental (Goda et al, 2022).…”
Section: Discussionunclassified
“…The design matrix with 12 trials along with two core trials to identify human error, the response that was observed (agarase production), and three levels for the chosen parameters, denoted as high (+ 1), medium (0), and low (− 1) all are displayed in Table 3 . The model was implemented using the coefficient outcomes of each factor 48 , 49 .…”
Section: Methodsmentioning
confidence: 99%
“…The global production of chicken feathers has been estimated to reach millions of tons annually. [ 8 ] Traditional treatment approaches fail to enable the high‐value utilization of chicken feather waste, with only a small fraction of feathers currently being recycled. [ 9 ] For instance, some feathers are employed in the production of down jackets owing to their exceptional thermal insulation properties, while others are converted into feather meal or fertilizers for animal husbandry and agriculture owing to their rich protein content.…”
Section: Introductionmentioning
confidence: 99%